Documentation of ethnomedicinal orchids from Jammu and Kashmir, India - Thakur, Sajan; Sharma, Udhay; Singh , Sunit; Dutt , Harish Chander (Ecological Questions, 2024)
Orchids are a group of plants famous for their showy and beautiful flowers. Besides their aesthetic value, these are also used traditionally for their ethnomedicinal properties. In Jammu and Kashmir, India, 21 orchid species from 17 different genera have been documented for their utilization as ethnomedicinal plants. Rhizomes and tubers of these orchids are the main plant parts to be used to cure many disorders like gastro-intestinal, skeleton-muscular, neurological and others.